Self-Efficacy and Learning Motivation as Predictors of Geography Academic Performance - Fajri Irfani Riswan; Yunus Aris Wibowo; Ratih Puspita Dewi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze the correlation between self-efficacy and learning motivation on student performance in geography at SMA Negeri 1 Cawas, Klaten Regency.Methodology: This study was conducted at SMA Negeri 1 Cawas using descriptive quantitative methods and data analysis using multiple correlations.Results: The findings show that the self-efficacy index is 75.85%, and the learning motivation index is 87.89%, both of which are relatively high. As many as 81% of students have high learning outcomes. Multiple correlation analysis shows a strong and significant relationship (R = 0.800; Sig. = 0.000) between self-efficacy, motivation, and learning outcomes. Applications/Originality/Value: These findings emphasize the importance of building self-confidence and motivation to improve academic achievement, which requires learning strategies that support students' psychological readiness to study geography.